2014
DOI: 10.1080/10508422.2014.920707
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Ambiguities in Participatory Action Research With Unauthorized Migrants

Abstract: There is increased recognition of the importance of well-designed scholarship on how immigration status and policies impact migrants in the United States, including those who are unauthorized. Some researchers have looked to community-based and participatory methods to develop trust, place migrants' voices at the forefront, and engage collaboratively in using research as a tool for social change. This article reviews three ethical ambiguities that emerged in the process of a series of participatory action rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Some scholars (Brabeck et al, 2015) have argued that approaches such as participatory action research (PAR) offer strategies for both research and advocacy because they position participants as coresearchers and agents in discovering the structural roots of the inequalities they experience, and lead to the identification of action steps to address those inequalities. Youth participatory action research (yPAR) employs creative methods, such as storytelling, photovoice, and participatory drama and helps youth to connect their individual realities to broader, systemic and historical factors, and to organize collective action toward change (Day, Charles, & Rose, 2013).…”
Section: Methodological and Ethical Challenges To Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars (Brabeck et al, 2015) have argued that approaches such as participatory action research (PAR) offer strategies for both research and advocacy because they position participants as coresearchers and agents in discovering the structural roots of the inequalities they experience, and lead to the identification of action steps to address those inequalities. Youth participatory action research (yPAR) employs creative methods, such as storytelling, photovoice, and participatory drama and helps youth to connect their individual realities to broader, systemic and historical factors, and to organize collective action toward change (Day, Charles, & Rose, 2013).…”
Section: Methodological and Ethical Challenges To Researchmentioning
confidence: 99%
“…Third, immigrant children and parents are linguistically and culturally diverse (e.g., they may be members of indigenous communities whose first language is not Spanish), calling into question the reliability and validity of our measurement instruments. Fourth, individuals who have not been apprehended or detained have valid concerns about discovery and therefore may decline to participate in research, limiting the generalizability of study findings (Brabeck, Lykes, Sibley, & Kene, 2015). Finally, access to children is dependent upon access to parents or the state for consent.…”
mentioning
confidence: 99%
“…However, despite its many strengths, the photovoice method is not without limitations, including several ethical concerns that have been raised in recent years (Brabeck et al, 2015; Creighton et al, 2018; Evans-Agnew & Rosemberg, 2016; Johnston, 2016; Murray & Nash, 2017; Sanon et al, 2014; Shankar, 2016). Because such concerns limit the advancement of equitable research, four of them are briefly discussed below.…”
Section: Photovoice Limitations: Ethical Concernsmentioning
confidence: 99%
“…Brabeck et al (2015) suggested power differentials can lead to altruistic action, which may seem beneficial on the surface, but can present ethical dilemmas. It may be unethical not to use researcher resources and privilege to address community injustice, yet it may be equally unethical for researchers to unintentionally raise false hope (Brabeck et al, 2015). The assumption that redistribution of power can be achieved among partnership members through the CBPR approach might not always be possible due to power hierarchies in the community and in the research partnership, and due to individual and community capacity to participate.…”
Section: Partnership Collaboration and Powermentioning
confidence: 99%